Analysis of calcium (Ca) and phosphorus (P) levels in meti shells (Batissa violacea L.) - Yadi Sumarsono; Baharuddin Hamzah; Reny Reny (Jurnal Akademika Kimia, 2024)
Meti clams (Batissa violacea L) are one of the types of shellfish that live in freshwater. Shell waste contains high levels of calcium carbonate (98% by weight) and has potential for utilization. This research aims to determine the calcium (Ca) and phosphorus (P) levels in meti shells (Batissa violacea L.) from Woomparigi Village, North Morowali Regency. Analysis of calcium levels (Ca) using an atomic absorption spectrophotometer (AAS) at wavelengths of 422.7nm and phosphorus levels (P) using a UV-Vis spectrophotometer at a wavelength of 590nm. The results show that the average concentration of Calcium (Ca) is 14.58%, while the average concentration of Phosphorus (P) is 2.01%.